10-Year Molecular Surveillance of Listeria monocytogenes Using Whole-Genome Sequencing in Shanghai, China, 2009–2019 - Zhang, Hongzhi; Chen, Weijie; Wang, Jing; Xu, Biyao; Liu, Hong; Dong, Qingli; Zhang, Xi (Frontiers in Microbiology, 2020)
Listeria monocytogenes is the etiologic agent of listeriosis, and has emerged as an important foodborne pathogen worldwide. In this study, the molecular characteristics of 155 L. monocytogenes isolates from seven groups in 22 categories in Shanghai, the biggest city in China, were identified using whole-genome sequencing (WGS). Most of these L. monocytogenes isolates (79.3%) were obtained between May and October from 2009 to 2019. Serogroups and clonal complexes (CCs) of L. monocytogenes were found to be useful for the identification of potential health risks linked to foods. Differences in the distributions of serogroups and CCs among different food groups were analyzed using two-tailed tests using SPSS software. Results showed that the IIa serogroup was identified among most of food groups. However, the prevalence of serogroups IIb and IVb was higher significantly in Ready-to-Eat (RTE) foods than in other food groups, as the same with group IIc in raw meat than others. Meanwhile, the prevalence of CC9 and CC121 in raw meat, CC8 in raw poultry and CC87 in raw seafood was higher significantly than in other food groups. Especially, CC87 was the predominant CC in foodborne and clinical isolates in China, indicating that raw seafood might present a high risk to food safety. Furthermore, hypervirulence pathogenicity islands LIPI-3 and LIPI-4 were found in ST3, ST1 and ST87, respectively. And the clonal group CC619 carried both LIPI-3 and LIPI-4, as previously reported in China. Core genome multilocus sequence typing (cgMLST) analysis suggested that CC87 isolates from the same food groups in different years had no allelic differences, indicating that L. monocytogenes could persistent over years. These ten-year results in Shanghai underscore the importance of molecular epidemiological surveillance of L. monocytogenes in foodborne products to assess the potential risk of this pathogen, and further address food safety issues in China.